Simvastatin Treatment Upregulates HO-1 in Patients with Abdominal Aortic Aneurysm but Independently of Nrf2. (20th March 2018) - Piechota-Polanczyk, Aleksandra; Kopacz, Aleksandra; Kloska, Damian; Zagrapan, Branislav; Neumayer, Christoph; Grochot-Przeczek, Anna; Huk, Ihor; Brostjan, Christine; Dulak, Jozef; Jozkowicz, Alicja
Abstract : Heme oxygenase-1 (HO-1), encoded by HMOX1 gene and regulated by Nrf2 transcription factor, is a cytoprotective enzyme. Its deficiency may exacerbate abdominal aortic aneurysm (AAA) development, which is also often associated with hyperlipidemia. Beneficial effects of statins, the broadly used antilipidemic drugs, were attributed to modulation of Nrf2/HO-1 axis. However, the effect of statins on Nrf2/HO-1 pathway in patients with AAA has not been studied yet. We analyzed AAA tissue from patients treated with simvastatin ( N = 28) or without statins ( N = 14). Simvastatin treatment increased HO-1 protein level in AAA, both in endothelial cells (ECs) and in smooth muscle cells (SMCs), but increased Nrf2 localization was restricted only to vasa vasorum. Nrf2 target genes HMOX1, NQO1, and GCLM expression remained unchanged in AAA. In vitro studies showed that simvastatin raises HO-1 protein level slightly in ECs and to much higher extent in SMCs, which is not related to Nrf2/ARE activation, although HMOX1 expression is upregulated by simvastatin in both cell types. In conclusion, simvastatin-induced modulation of HO-1 level in ECs and SMCs in vitro is not related to Nrf2/ARE activity. Likewise, divergent HO-1 and Nrf2 localization together with stable expression of Nrf2 target genes, including HMOX1, in AAA tissue denotes Nrf2 independency.